HARGA, DESIGN, KUALITAS PRODUK DAN PROMOSI PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN MOBIL SUZUKI APV DI DEALER TOP MOTOR BATU BULAN - Wiryawan Suputra Gumi; Galuh Nanda Apriyanto (Forum Manajemen STIMI Handayani Denpasar, 2021)
The purpose of this study was to determine the effect of Price, Design, Product Quality and Promotion on Purchasing Decisions of Suzuki APV Cars. This research was conducted at the Top Motor Dealer Batu Bulan. The population in this study were 150 Suzuki APV buyers at Batu Bulan Motor Top Dealers in 2019. The sample was selected using the Slovin formula and the number of samples was 109 respondents. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that 1) Price has a positive and significant effect on purchasing decisions; 2) Design has a positive and significant effect on purchasing decisions; 3) Product quality has a positive and significant effect on purchasing decisions; 4) Promotion has a positive and significant effect on purchasing decisions; 5) Price, design, product quality and promotion influence purchasing decisions.